Ionising radiation from diagnostic x rays in very low birthweight babies. Issue 3 (1st May 1998) - Sutton, P M; Arthur, R J; Taylor, C; Stringer, M D
Abstract : AIM: To quantify the exposure of very low birthweight neonates to ionising radiation from diagnostic x -rays. METHODS: Retrospective analysis was made of all radiographs performed over 18 months in an integrated special care baby unit and regional neonatal surgical unit in a large teaching hospital of surviving inborn babies of very low birthweight (<1500 g) admitted to the unit. RESULTS: Fifty five VLBW neonates were treated for a total of 3296 days and received 498 radiographs (median 5 per infant). The mean effective radiation dose was 0.04 mSv and the maximum for one infant was 0.54 mSv. CONCLUSIONS: The radiation burden in this group of neonates is low and the benefits of diagnostic radiographs far outweigh any potential radiation risks.